An Application of Differential Transform Method for Optimal Control Problems (Journal of the College of Basic Education, 2022)
In this paper, a numerical method is presented for finding the solution of some optimal control problems. Finding the solution of these problems need to solve the corresponding ordinary differential equations which are generally nonlinear. Indirect method is used in this work with the aid of differential transform method (DTM) for solving optimal control problems (OCPs). Since this method gives a closed form solution of the problem and avoids the round off errors, it can be considered as an efficient method for solving various kind of problems. Some examples are presented to show the efficiency of the proposed technique.